1997
DOI: 10.1021/jo962252h
|View full text |Cite
|
Sign up to set email alerts
|

Tandem β-Fragmentation−Hydrogen Abstraction Reaction of Alkoxy Radicals in Steroidal Systems

Abstract: A number of tertiary or hemiacetalic steroidal alcohols, 2-hydroxy-3,4-dinor-2,3-secocholestan-5-one 2,5-hemiacetal (1), 2beta,3beta-dihydro-3'H-cyclopropa[2,3]-cholestan-5alpha-ol (7), 3beta-phenyl-5alpha-hydroxycholestan-2-one (10), 5alpha-hydroxycholestan-3-one (15), 3beta,5alpha-dihydroxycholestan-7-one 3-acetate (21), and 4,4-dimethyl-19-hydroxy-5alpha-cholestan-3-one 19,3-hemiacetal (27) have been prepared in order to test a new tandem beta-fragmentation-hydrogen abstraction reaction. The alkoxy radicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The 13 C NMR data of ring A in 2 were similar to those in 1. Comparison of the 13 C NMR spectroscopic data in CDCl 3 of 2 with those of the moiety of ring A of β-hydroxy-5α,6α-epoxycholesta-7-one [9] suggested the trans-fused junction for rings A/B and the α-orientation for the epoxy unit at C-5/C-6. The ROESY correlation found between δ 1.38 (1H, m, H axial -1) and 3.58 (1H, m, H-3) indicated the β-orientation for the hydroxyl at C-3, while the ROESY correlation found between δ 0.83 (3H, s, H-18) and 2.11 (1H, m, H-20) indicated the β-orientation for the side chain at C-17.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The 13 C NMR data of ring A in 2 were similar to those in 1. Comparison of the 13 C NMR spectroscopic data in CDCl 3 of 2 with those of the moiety of ring A of β-hydroxy-5α,6α-epoxycholesta-7-one [9] suggested the trans-fused junction for rings A/B and the α-orientation for the epoxy unit at C-5/C-6. The ROESY correlation found between δ 1.38 (1H, m, H axial -1) and 3.58 (1H, m, H-3) indicated the β-orientation for the hydroxyl at C-3, while the ROESY correlation found between δ 0.83 (3H, s, H-18) and 2.11 (1H, m, H-20) indicated the β-orientation for the side chain at C-17.…”
Section: Resultsmentioning
confidence: 98%
“…When 10-CH 3 and 7-H were both in pseudo-axial positions of the boat, the distance between 19-H and 7-H was close enough to produce the ROESY correlation. Comparison of the 13 C NMR spectroscopic data in CDCl 3 of 1, with those of the moiety of ring A of 3β-hydroxy-5α,6α-epoxycholesta-7-one, [9] suggested the trans-fused junction for rings A/B and the α-orientation for the epoxy unit at C-5/C-6, which indicated that the boat of ring B of 1 was the endo-boat form. The deduction that 10-CH 3 and 7-H were both in pseudo-axial positions of the boat indicated that the methoxyl at C-7 was in α-orientation.…”
Section: Resultsmentioning
confidence: 99%
“…A distinctly different reaction cascade leading to tetrahydrofurans is illustrated in Scheme 40 [74]. It was proposed that these reactions proceed by iodine-mediated deoxygenation of the peroxyl radical to an slkoxyl radical, which undergoes intramolecular C-H abstraction to form a /?-keto radical [74].…”
Section: Oxygenation Of Cycloalkanols and Related Compoundsmentioning
confidence: 99%
“…It was proposed that these reactions proceed by iodine-mediated deoxygenation of the peroxyl radical to an slkoxyl radical, which undergoes intramolecular C-H abstraction to form a /?-keto radical [74]. Elimination of an Mhydrogen atom generates an enone, which is ultimately captured intramolecularly by conjugate hydroxyl addition to give a tetrahydrofuran (Scheme 40).…”
Section: Oxygenation Of Cycloalkanols and Related Compoundsmentioning
confidence: 99%
“…We have used it in a one-step synthesis of A and A' rings of the tetranortriterpene limonene and related compounds (Eq. 19, Scheme 6) [48].…”
Section: Fragmentation Of Hemiacetalsmentioning
confidence: 99%